Overview of Student Level Knowledge IV About Basic Living Assistance (BHD) Study Program Ners STIKes Santa Elisabeth - Ice Septriani Saragih; Vina YS. Sigalingging; Mestiana Br. Karo; Reza T. Br. Ginting (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Basic Life Support is a series of first aid measures that can be carried out by anyone to help save the life of someone who is experiencing a life-threatening condition such as cardiac arrest, choking, or not breathing normally. Students are a community group that has great potential to become agents of change in handling emergency conditions. They have access to good information and education, and tend to have a high sense of social responsibility. Therefore, a good understanding of BHD among students is very important. Good knowledge of BHD allows them to act quickly and appropriately in emergency situations, thereby increasing the survival rate of victims of sudden cardiac arrest and other medical emergencies. The aim of the research is to determine the description of level IV students' knowledge about Basic Life Support (BHD) in the Santa Elisabeth Medan STIKes Nursing Study Program in 2024. This research method is descriptive. The sample in this research was 98 respondents. The sampling in this research was Total Sampling. This research instrument uses a questionnaire. The research results showed that the majority of respondents had knowledge in the good category, 93 respondents (94.9%). With these results, it is hoped that respondents can maintain and continue to increase their knowledge about BHD. It is hoped that BHD can be used as a core curriculum in health institutions.